Fertility Desires of HIV-positive Women Attending Care and Treatment Clinics (CTC) in Urban Areas in Tanzania - Aleswa Zebedayo; Oscar Mukasa; Samwel Analanga; Irene Moshi; Ibrahim Msuya; Francis Levira (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Reproductive concerns by People Living with HIV (PLHIV) are matters that are important for both individual and general public health. We described fertility desire among HIV-positive women attending Care and Treatment Clinics (CTC) and determined factors for having such a desire to get children in urban areas of Dar es Salaam and Dodoma in Tanzania. Material and Methods: Cross-sectional study for which primary data were collected in a random sample of women of reproductive age (15-49 years) after accessing HIV care and treatment services. A survey was conducted among HIV-positive women receiving anti-retroviral treatment to document service needs, service quality, and fertility preferences. A Univariate model was used to examine the relationship between the dependent and the independent variables, and all associations were taken into account in the final model. Results: Among 691 participants, 282 (40.8%) women living with HIV have fertility desire. Women aged above 25 experienced a reduction in the odds of fertility desire by 56% (P value =0.003) compared to the reference group of women aged 25 years or less. Fertility desire was predicted to have two times as much growth with 1 to < 3 years (p- value=0.02) and 5 or 5+ years (P value =0.01) time lapse since the debut of ART, compared to the group of women who were on ART for 3 years but less than five years. Conclusion: Our data has not only reconfirmed the importance of ART and PMTCT services to PLHIV but also contributed to evidence on their value addition in terms of the creation of resilience to normal fertility family life after debut HIV diagnosis.